SMN1 copy-number and sequence variant analysis from next-generation sequencing data. - López-López, Daniel; Loucera, Carlos; Carmona, Rosario; Aquino, Virginia; Salgado, Josefa; Pasalodos, Sara; Miranda, María; Alonso, Ángel; Dopazo, Joaquin (Hum Mutat, 2020)
Spinal muscular atrophy (SMA) is a severe neuromuscular autosomal recessive disorder affecting 1/10,000 live births. Most SMA patients present homozygous deletion of SMN1, while the vast majority of SMA carriers present only a single SMN1 copy. The sequence similarity between SMN1 and SMN2, and the complexity of the SMN locus makes the estimation of the SMN1 copy-number by next-generation sequencing (NGS) very difficult. Here, we present SMAca, the first python tool to detect SMA carriers and estimate the absolute SMN1 copy-number using NGS data. Moreover, SMAca takes advantage of the knowledge of certain variants specific to SMN1 duplication to also identify silent carriers. This tool has been validated with a cohort of 326 samples from the Navarra 1000 Genomes Project (NAGEN1000). SMAca was developed with a focus on execution speed and easy installation. This combination makes it especially suitable to be integrated into production NGS pipelines. Source code and documentation are available at https://www.github.com/babelomics/SMAca.
Keywords: Base Sequence; DNA Copy Number Variations; High-Throughput Nucleotide Sequencing; Humans; Reproducibility of Results; Software; Survival of Motor Neuron 1 Protein

VISMapper: ultra-fast exhaustive cartography of viral insertion sites for gene therapy. - Juanes, José M; Gallego, Asunción; Tárraga, Joaquín; Chaves, Felipe J; Marin-Garcia, Pablo; Medina, Ignacio; Arnau, Vicente; Dopazo, Joaquin (BMC Bioinformatics, 2017)
BACKGROUND: The possibility of integrating viral vectors to become a persistent part of the host genome makes them a crucial element of clinical gene therapy. However, viral integration has associated risks, such as the unintentional activation of oncogenes that can result in cancer. Therefore, the analysis of integration sites of retroviral vectors is a crucial step in developing safer vectors for therapeutic use. RESULTS: Here we present VISMapper, a vector integration site analysis web server, to analyze next-generation sequencing data for retroviral vector integration sites. VISMapper can be found at: http://vismapper.babelomics.org . CONCLUSIONS: Because it uses novel mapping algorithms VISMapper is remarkably faster than previous available programs. It also provides a useful graphical interface to analyze the integration sites found in the genomic context.
Keywords: Base Sequence; Genetic Therapy; Genetic Vectors; High-Throughput Nucleotide Sequencing; Humans; Internet; User-Computer Interface; Virus Integration

A Pan-Cancer Catalogue of Cancer Driver Protein Interaction Interfaces. - Porta-Pardo, Eduard; García-Alonso, Luz; Hrabe, Thomas; Dopazo, Joaquin; Godzik, Adam (PLoS Comput Biol, 2015)
Despite their importance in maintaining the integrity of all cellular pathways, the role of mutations on protein-protein interaction (PPI) interfaces as cancer drivers has not been systematically studied. Here we analyzed the mutation patterns of the PPI interfaces from 10,028 proteins in a pan-cancer cohort of 5,989 tumors from 23 projects of The Cancer Genome Atlas (TCGA) to find interfaces enriched in somatic missense mutations. To that end we use e-Driver, an algorithm to analyze the mutation distribution of specific protein functional regions. We identified 103 PPI interfaces enriched in somatic cancer mutations. 32 of these interfaces are found in proteins coded by known cancer driver genes. The remaining 71 interfaces are found in proteins that have not been previously identified as cancer drivers even that, in most cases, there is an extensive literature suggesting they play an important role in cancer. Finally, we integrate these findings with clinical information to show how tumors apparently driven by the same gene have different behaviors, including patient outcomes, depending on which specific interfaces are mutated.
Keywords: Animals; Base Sequence; Biomarkers, Tumor; Catalogs as Topic; Chromosome Mapping; Computer Simulation; DNA Mutational Analysis; Genetic Predisposition to Disease; Humans; Models, Genetic; Molecular Sequence Data; mutation; Neoplasm Proteins; Neoplasms; Polymorphism, Single Nucleotide; Protein Interaction Mapping; Signal Transduction

Re-evaluation casts doubt on the pathogenicity of homozygous USH2A p.C759F. - Pozo, María González-Del; Bravo-Gil, Nereida; Méndez-Vidal, Cristina; Montero-de-Espinosa, Ignacio; Millán, José M; Dopazo, Joaquin; Borrego, Salud; Antiňolo, Guillermo (Am J Med Genet A, 2015)
Mutations in USH2A are a common cause of Retinitis Pigmentosa (RP). Among the most frequently reported USH2A variants, c.2276G>T (p.C759F) has been found in both affected and healthy individuals. The pathogenicity of this variant remains controversial since it was detected in homozygosity in two healthy siblings of a Spanish family (S23), eleven years ago. The fact that these individuals remain asymptomatic today, prompted us to study the presence of other pathogenic variants in this family using targeted resequencing of 26 retinal genes in one of the affected individuals. This approach allowed us to identify one novel pathogenic homozygous mutation in exon 13 of PDE6B (c.1678C>T; p.R560C). This variant cosegregated with the disease and was absent in 200 control individuals. Remarkably, the identified variant in PDE6B corresponds to the mutation responsible of the retinal degeneration in the naturally occurring rd10 mutant mice. To our knowledge, this is the first report of the identification of the rd10 mice mutation in a RP family. These findings, together with a review of the literature, support the hypothesis that homozygous p.C759F mutations are not pathogenic and led us to exclude the implication of p.C759F in the RP of family S23. Our results indicate the need of re-evaluating all families genetically diagnosed with this mutation.
Keywords: Base Sequence; Cyclic Nucleotide Phosphodiesterases, Type 6; Extracellular Matrix Proteins; Gene Library; Humans; Molecular Sequence Data; Mutation, Missense; Pedigree; Retinitis pigmentosa; Sequence Analysis, DNA; Spain

Exome sequencing reveals novel and recurrent mutations with clinical significance in inherited retinal dystrophies. - González-del Pozo, María; Méndez-Vidal, Cristina; Bravo-Gil, Nereida; Vela-Boza, Alicia; Dopazo, Joaquin; Borrego, Salud; Antiňolo, Guillermo (PLoS One, 2014)
This study aimed to identify the underlying molecular genetic cause in four Spanish families clinically diagnosed of Retinitis Pigmentosa (RP), comprising one autosomal dominant RP (adRP), two autosomal recessive RP (arRP) and one with two possible modes of inheritance: arRP or X-Linked RP (XLRP). We performed whole exome sequencing (WES) using NimbleGen SeqCap EZ Exome V3 sample preparation kit and SOLID 5500xl platform. All variants passing filter criteria were validated by Sanger sequencing to confirm familial segregation and the absence in local control population. This strategy allowed the detection of: (i) one novel heterozygous splice-site deletion in RHO, c.937-2_944del, (ii) one rare homozygous mutation in C2orf71, c.1795T>C; p.Cys599Arg, not previously associated with the disease, (iii) two heterozygous null mutations in ABCA4, c.2041C>T; p.R681* and c.6088C>T; p.R2030*, and (iv) one mutation, c.2405-2406delAG; p.Glu802Glyfs*31 in the ORF15 of RPGR. The molecular findings for RHO and C2orf71 confirmed the initial diagnosis of adRP and arRP, respectively, while patients with the two ABCA4 mutations, both previously associated with Stargardt disease, presented symptoms of RP with early macular involvement. Finally, the X-Linked inheritance was confirmed for the family with the RPGR mutation. This latter finding allowed the inclusion of carrier sisters in our preimplantational genetic diagnosis program.
Keywords: Adolescent; Adult; Amino Acid Sequence; Base Sequence; Child; Chromosome Segregation; DNA Mutational Analysis; Exome; Family; Female; Humans; Inheritance Patterns; Male; Middle Aged; Molecular Sequence Data; mutation; Pedigree; Retinal Dystrophies; Rhodopsin

Novel RP1 mutations and a recurrent BBS1 variant explain the co-existence of two distinct retinal phenotypes in the same pedigree. - Méndez-Vidal, Cristina; Bravo-Gil, Nereida; González-del Pozo, María; Vela-Boza, Alicia; Dopazo, Joaquin; Borrego, Salud; Antiňolo, Guillermo (BMC Genet, 2014)
BACKGROUND: Molecular diagnosis of Inherited Retinal Dystrophies (IRD) has long been challenging due to the extensive clinical and genetic heterogeneity present in this group of disorders. Here, we describe the clinical application of an integrated next-generation sequencing approach to determine the underlying genetic defects in a Spanish family with a provisional clinical diagnosis of autosomal recessive Retinitis Pigmentosa (arRP). RESULTS: Exome sequencing of the index patient resulted in the identification of the homozygous BBS1 p.M390R mutation. Sanger sequencing of additional members of the family showed lack of co-segregation of the p.M390R variant in some individuals. Clinical reanalysis indicated co-ocurrence of two different phenotypes in the same family: Bardet-Biedl syndrome in the individual harboring the BBS1 mutation and non-syndromic arRP in extended family members. To identify possible causative mutations underlying arRP, we conducted disease-targeted gene sequencing using a panel of 26 IRD genes. The in-house custom panel was validated using 18 DNA samples known to harbor mutations in relevant genes. All variants were redetected, indicating a high mutation detection rate. This approach allowed the identification of two novel heterozygous null mutations in RP1 (c.4582_4585delATCA; p.I1528Vfs*10 and c.5962dupA; p.I1988Nfs*3) which co-segregated with the disease in arRP patients. Additionally, a mutational screening in 96 patients of our cohort with genetically unresolved IRD revealed the presence of the c.5962dupA mutation in one unrelated family. CONCLUSIONS: The combination of molecular findings for RP1 and BBS1 genes through exome and gene panel sequencing enabled us to explain the co-existence of two different retinal phenotypes in a family. The identification of two novel variants in RP1 suggests that the use of panels containing the prevalent genes of a particular population, together with an optimized data analysis pipeline, is an efficient and cost-effective approach that can be reliably implemented into the routine diagnostic process of diverse inherited retinal disorders. Moreover, the identification of these novel variants in two unrelated families supports the relatively high prevalence of RP1 mutations in Spanish population and the role of private mutations for commonly mutated genes, while extending the mutational spectrum of RP1.
Keywords: Bardet-Biedl Syndrome; Base Sequence; Case-Control Studies; DNA Mutational Analysis; Eye Proteins; Genes, Recessive; Genetic Association Studies; Humans; Microsatellite Repeats; Microtubule-Associated Proteins; Mutation, Missense; Pedigree; Phenotype; Retina; Retinitis pigmentosa

PhylomeDB: a database for genome-wide collections of gene phylogenies. - Huerta-Cepas, Jaime; Bueno, Anibal; Dopazo, Joaquin; Gabaldón, Toni (Nucleic Acids Res, 2008)
The complete collection of evolutionary histories of all genes in a genome, also known as phylome, constitutes a valuable source of information. The reconstruction of phylomes has been previously prevented by large demands of time and computer power, but is now feasible thanks to recent developments in computers and algorithms. To provide a publicly available repository of complete phylomes that allows researchers to access and store large-scale phylogenomic analyses, we have developed PhylomeDB. PhylomeDB is a database of complete phylomes derived for different genomes within a specific taxonomic range. All phylomes in the database are built using a high-quality phylogenetic pipeline that includes evolutionary model testing and alignment trimming phases. For each genome, PhylomeDB provides the alignments, phylogentic trees and tree-based orthology predictions for every single encoded protein. The current version of PhylomeDB includes the phylomes of Human, the yeast Saccharomyces cerevisiae and the bacterium Escherichia coli, comprising a total of 32 289 seed sequences with their corresponding alignments and 172 324 phylogenetic trees. PhylomeDB can be publicly accessed at http://phylomedb.bioinfo.cipf.es.
Keywords: Base Sequence; Escherichia coli; Genes; Genomics; History, Ancient; Humans; Phylogeny; Proteins; Saccharomyces cerevisiae; Sequence Alignment